Gigantomastia in pregnancy with an accessory axillary mass masquerading as inflammatory carcinoma - Lokuhetty, M. D. S.; Saparamadu, P. A. M.; Al-Sajee, D. M. A.; Al-Ajmi, R. (Wiley-Liss, Inc., 2011)
Giagantomastia is a rare disorder known to occur in pregnancy, causing enlargement of the breasts greater than that of gravid enlargement. The histological features of gigantomastia are glandular hyperplasia and an increase of stromal tissue. Illustrated by one documented case, cytomorphology of gigantomastia was misdiagnosed as a phyllodes tumor. We document the cytomorphology of an axillary mass in a gravid woman of 24 years with gigantomastia. She presented in her first trimester with bilateral mastalgia and swelling, nonresponsive to antibiotics. Imaging excluded mass breast lesions and a pituitary prolactinoma. The breasts progressively enlarged, became warm, tender, and developed skin ulcerations and a peau d'orange appearance. Subsequently she developed a mass in her left axilla. On aspiration of the mass, some of the cytomorphological features were suspicious for a metastasis, which correlated well with her clinical features. Careful evaluation suggested cytomorphology to be compatible with benign accessory breast tissue with possible hormone related changes of pregnancy. Histology of the excised axillary mass confirmed this diagnosis. Thus, awareness of this rare condition and careful evaluation is mandatory to avoid misdiagnosis in a similar clinical context. Diagn. Cytopathol. 2011;39:141–143.